PEMBUATAN PUPUK ORGANIK CAIR MENGGUNAKAN TEKNOLOGI KOMPOSTING SEDERHANA - I.G.A. Kasmawan; G.N. Sutapa; I.M. Yuliara (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
Plants in growth and development require two types of nutrients, namely macro and micro nutrients.However, only N, P, and K elements are needed plants for larger amount. The purpose of this research is toprovide liquid organic fertilizer as balancing fertilizer considering the increasing price of fertilizer in themarket. Research on the use of simple composting technology in the manufacture of liquid organic fertilizeris done by involving participants from the elderly group, which is light and can be done alone. The composterused is a 25 L gallon with an outer connecting hose. The end of the hose is immersed in a bottle of water toensure the sustainability of the composting process in an anaerobic atmosphere. Production of liquid organicfertilizer using main ingredient in the form of foliage (5 kg) and livestock waste (1kg), with additivessuchshrimp paste (100 g) and brown sugar (200 g), and 200 mL EM4 as bioactivator. Five successful liquidorganic fertilizer products have the highest nitrogen (N), phosphorus (P), and potassium (K) content of0.16%, 153,75 mg/L and 663,98 mg/L, respectively.